2021
DOI: 10.3390/cells10010180
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Stromal Endometriosis in Thoracic Endometriosis

Abstract: Thoracic endometriosis (TE) is a rare type of endometriosis, where endometrial tissue is found in or around the lungs and is frequent among extra-pelvic endometriosis patients. Catamenial pneumothorax (CP) is the most common form of TE and is characterized by recurrent lung collapses around menstruation. In addition to histology, immunohistochemical evaluation of endometrial implants is used more frequently. In this review, we compared immunohistochemical (CPE) with histological (CPH) characterizations of TE/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 94 publications
1
10
0
Order By: Relevance
“…In a large systematic review, classic histologic findings for thoracic endometriosis were identified in only one-third of biopsied specimens [1 ▪▪ ]. Immunohistochemistry staining for ER, PR and CD10 may aid in the accurate diagnosis of thoracic endometriosis [17,18,19 ▪ ].…”
Section: Gold Standard Diagnosismentioning
confidence: 99%
“…In a large systematic review, classic histologic findings for thoracic endometriosis were identified in only one-third of biopsied specimens [1 ▪▪ ]. Immunohistochemistry staining for ER, PR and CD10 may aid in the accurate diagnosis of thoracic endometriosis [17,18,19 ▪ ].…”
Section: Gold Standard Diagnosismentioning
confidence: 99%
“…The most common location of endometriosis outside the abdominopelvic cavity is the thoracic cavity [6]. In 80% of cases, lesions are located on the right side [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of functional endometrial tissue in the thoracic cavity is called thoracic endometriosis syndrome (TES), an extremely rare disease with complex causes and pathogenesis that remains unclear [7,9], and can be classified as pulmonary or pleural [8]. The pathogenesis of this disease is still unknown although several concepts have been presented, but none of them can fully explain all the clinical manifestations of the syndrome [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations